Sensing of Metal Ions by Hybrid Systems of a Chiral Schiff Base Zn(II) Complex and Spiropyran - Aonuma, Masahiko; Onodera, Takashi; Morito, Satomi; Wada, Asami; Akitsu, Takashiro (Journal of Applied Solution Chemistry and Modeling, 2013)
We have constructed three (hybrid) systems for quantitative fluorescence sensing of metal ions by using chiral Schiff base Zn(II) complexes. System 1 is a hybrid system composed of a trans-type chiral Schiff base Zn(II) complex and merocyanine (Mc), which is open-form of spiropyran (Sp) after photoisomerization. Depending on intermolecular interactions and quenching, increase (Zn2+) or decrease (Cu2+ and Gd3+) of fluorescence intensity of Zn(II) complex could be observed as functions of concentration of metal ions. System 2 is a sole component of a salen-type chiral Schiff base Zn(II) complex which can coordinate metal ions. After coordination of Zn2+, Cu2+, and Gd3+ ions, decreasing of fluorescence intensity could be found for all the cases for system 2 under the same condition to system 1. System 3 is a hybrid system being consisted of a salen-type chiral Schiff base Zn(II) complex and Mc. Decrease or increase of fluorescence intensity is in agreement with intermolecular interactions, namely affinity for the Zn(II) complex is Zn2+ > Cu2+ > Gd3+, whereas it is reverse order for Mc. The quantitative spectroscopic nature (detected as absorption, CD, and fluorescence) of these systems is predominantly attributed to both organic ligands and Zn(II) center in a probe complex